Political dynasties and province creation - CHENG, Ranel Ram (KDI School, 2018)
This study explores the role of “political dynasties” in the creation of new provinces as a feature of decentralization reforms in the Philippines. This research looks into whether political dynasties are able to create new provinces through gerrymandering in order to achieve political ends, thus indicating local elite capture of decentralization reforms. Cooption of local elite families into representative institutions is a colonial legacy that manifests through the persistence of political dynasties in present-day institutions. By using historical institutionalism as analytical lens, key historical junctures in center-local relations were identified, parallel to the formation of the Philippine state, while situating local elite families within each juncture. In this way, this study distinguished between “Executive-led gerrymandering” and “Legislative-led gerrymandering” across different time periods. While the former fits the prevailing view of gerrymandering as a “strategic choice” of the central authority to accommodate rent-seeking by local elites, the latter shows how the Philippine Congress as an institution evolved as an amalgamation of local elites from across the country with the power to create the rules for decentralization, including that of province creation, to suit their own political interests in the first place.
Thesis(Master) --KDI School:Master of Public Policy,2018